Comparison of Figurative Language between Pop-Punk Songs Lyric by ”Paramore and Blink 182” - Erin Diniati Diniati; Fitrawati Fitrawati (English Language and Literature, 2017)
Figurative language is way to express an idea or concept through the usage of language. The aimed of this study was to find types of figurative language and the differences of figurative language used in pop-punk song lyric by Paramore and Blink 182. This paper only focuses on four common types of figurative language proposed by GorysKeraf (2009) in order to create the easier analysis.There are metaphor, simile, personification and hyperbole. The result of this research was the writer found 13figurative languages in Paramore songs lyric and 18figurative languages in Blink 182 songs lyric. The types of figurative language in Paramore were: Metaphor (10), Simile (1), Personification (1) and Hyperbole (1), while the types of figurative language in Blink 182 were: Metaphor (13), Simile (3), Personification (2), and there was no Hyperbole form. Based on the result finding, it can be concluded that Paramore and blink 182 more dominantly used metaphor expression in their lyric. Then Blink 182 used more figuratives language and poetic languang in their lyric than Paramore,although both of these band come from different generation, it doesn’t influence or change their style in using figurative language in their lyric, both of these pop-punk songs always used metaphor dominantly in their lyric.